Buku kanak-kanak: Analisis unsur Estetika - Arumugam, Kaithiri (Universiti Pendidikan Sultan Idris, UPSI, 2019)
Children's books are always a place for kids and adults alike. This is because, children's books have elements of beauty or aesthetics that contribute to the language aspect of the reader. Nevertheless, books published by publishers in Malaysia as reading material to stimulate children's reading and enjoyment have not been compared to books published by publishers from abroad (Alimah Salam, 2010: 39). Therefore, the purpose of this paper is to address the issue of aesthetics in children's books in Malaysia. The objectives of this study were to identify the aesthetic elements in children's books and to analyze the aesthetic elements in children's books.This study uses content analysis methods by examining nine children's books based on the aesthetic approach proposed by Maria Nikolajeva (2001). The findings show that there are two aesthetic elements in children's books, namely genre aesthetics and language aesthetics.